Influência de cores de E.P.Is (calças e luvas) na defensividade das Abelhas Africanizadas (Apis melífera L.) - Dias, Victor Hugo Pedraça (2015)
Scientific works on the defensive behavior of AHB-Africanized Honey Bees (A. mellifera L). show that they are more sensitive to dark color. Thus, the use of clothing and gloves with light colors should be an effective strategy to reduce defensiveness of these bees. However many beekeepers still use protective equipments not suitable as dark pants, dark gloves etc. This work aims to evaluate the influence of the colors of pants and gloves on defensiveness of AHB in order to guide the beekeepers about the most suitable protective clothing and gloves for handling these bees. The study was conducted at the CETAPIS bee yards, Experimental Station of UFERSA,in Mossoró-RN from September 2013 to May 2015. Three Langstroth hives were chosen, over 60 thousand bees each, with a high degree of defensive behavior (value of 4 on a scale of 1 to 4). For defensiveness testing the hives were handled without the use of smoke and the hives were stimulated with beats at the entrance and on the sides of the hives. After the bees became angry photographs of the experimenters were done. They wore three colored clothing (white, light blue and dark blue) and wore white gloves, yellow and dark green. The experimenters were posted in front of the hive for about 15 minutes for the photos. A white screen was placed (cloth) behind the experimenters to allow identification of bees around the body of the experimenters, pants and gloves. Each test was conducted four times throughout the day for each hive and for three consecutive days. 1059 comparative photos of pants and 4515 photos of the gloves were made. Photos of each comparative test were chosen at random among the best sharper photos. For comparisons were analyzed 36 photos of pants and 36 photos of the gloves. Bees were counted with the help of the program "Paint". For scores of bees identical areas were defined for each variable and all the bees were counted within their respective areas. The data were transformed to ensure normal distribution. The Tuckey test with 99% confidence level was applied. The white pants attracted an average of 40.28 +5.17 bees, light blue pants attracted 222.77 + 27.55 bees and dark blue pants attracted 392.60 + 78.67 bees. There was a statistically significant difference between the averages for the three treatments. As gloves, dark green attracted an average of 225.72 +35.99 bees, white gloves attracted 77.45 + 26.80 bees and yellow gloves attracted 99.20 + 22 82 bees. The differences between the three means were statistically significant, but there was no statistically significant difference between yellow and white. The results clearly demonstrated that the protective cloths (dark coloration pants) and dark green gloves attract more bees, which become more defensive. This experiment proved that the light-colored protective cloths were the most recommended in the management of Africanized bees, and one should avoid using dark clothes (pants, blouses, coats, overalls) and dark gloves.